Strategi Pembudidayaan Melinjo Sebagai Penghijauan dan Peningkatan Pendapatan Masyarakat di Kabupaten Batubara - Puguh Irfan; Syaad Afifuddin; Miftahuddin Miftahuddin (Universitas Medan Area, 2018)
three highest priority The strategy in plant breeding strategies of melinjo as reforestation and increasing incomes at Batubara District that can be taken are : (1) the greening implement with melinjo plants; (2) improve the greening funds through the participation of private sector and non-governmental; (3) the increase of motivation and participation.The income directly influence the level of public life itself, and is often associated with life prevailing in society. The revenue shows that a person's level of ability their needs.The result of studies shows that the primary income of farmer sample average Rp. 2.276.371,-/month, and additional income from the melinjo cultivation the lowest is Rp. 96.000,-/month by the number of trees as much as 2 trees, and the highest income is Rp. 2.082.167,-/month with 31 trees. The income average of Rp. 47.447,-/trees/month. The green space (greening) at the Batubara District until the year 2009 are 14.174 ha or 15% of the area of Batubara District. The greening at Batubara District still use shade unproductive trees, therefore the need to use the productive tree in this case is still very large like melinjo trees at Batubara District and also an opportunity to utilize the productions of the tree to add melinjo income apart from the benefits of greening itself. Keywords : Melinjo, motivation, greening.